First Nations Gaming as a Self-Government Imperative: Ensuring the Health of First Nations Problem Gamblers - Belanger, Yale (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2010)
AbstractAt the end of 2008, there were 17 First Nations casinos operating in Canada. Recent statistics confirm that all are money-making enterprises, and that individual First Nations are using the money to improve social programming and augment infrastructure. What has been overlooked to date is local health: specifically, limited funding was set aside in all Province-First Nations gaming agreements to implement problem-gambling treatment programs for on-reserve residents negatively influenced by the introduction of a casino. This is surprising considering that several studies in Canada and the United States have shown Aboriginal people are more likely to become problem gamblers. This paper argues that by situating a casino in a reserve community, the host community establishes an imperative to treat those negatively affected by ease of access to casino gambling games. To do so is an aspect of self-determination, and a responsibility First Nations assume when selecting casinos as mechanisms of economic development.